Increase of Urinary 5-Hydroxyindoleacetic Acid Excretion but Not Serum Chromogranin a Following Over-The-Counter 5-Hydroxytryptophan Intake - Tisha Joy; Grace Walsh; Sonya Tokmakejian; Stan HM Van Uum (Canadian Journal of Gastroenterology)
BACKGROUND: 5-hydroxyindoleacetic acid (5-HIAA) excretion is commonly measured for biochemical detection of carcinoid tumours. A 77-year-old woman was referred for elevated 24 h urine 5-HIAA excretion (510 μmol/day; normal is less than 45 μmol/day) and serum chromogranin A (CgA) (72.1 U/L; normal is less than 18 U/L), both subsequently normalized after discontinuation of 5-hydroxytryptophan (5-HTP). 5-HTP, a precursor of serotonin, is not commonly listed as a substance that increases 5-HIAA levels in urine. The effect of 5-HTP on CgA has not been previously described.